NEW PATHOGENIC MECHANISMS OF THE CHRONIC PERICARDITIS - V. V. Kochmasheva; E. D. Rozhdestvenskaya; E. S. Belikov; M. A. Dergunova; M. V. Arhipov (Рациональная фармакотерапия в кардиологии)
Aim. To determine the main mechanisms of chronic pericarditis (CP) on the basis of chronic pericardium inflammation study with morphological, laboratory and instrumental methods.Material and methods. 139 patients with CP were involved in the study. The analysis of clinical data, results of laboratory and instrumental examination as well as morphological data of 27 pericardectomies was performed.Results. The morphological features in 92,5% of cases did not depend on disease aetiology. Inflammation signs are founded in 74,1% of pericardium samples. Inflammatory reaction of adjacent fatty tissue and changes of the pericardium nervous system also was revealed. The levels of immune status markers in patients with CP significantly depended on inflammation activity and they did not depend on disease causes. Anti-inflammatory cytokine levels (receptor antagonist of IL-1 alpha (RAIL-1 alpha) above 700 pg/ml is founded in patients with subclinical disease feature. RAIL level below 300 pg/ml took place in serious and recurring CP.Conclusion. CP is a result of pericardium inflammation with involving adjacent fatty tissue and with changes of the pericardium nervous system. Relationship between disease clinical course and RAIL-1 level was found. CP progression and new pathogenesis mechanisms is discussed.